Congenital intrinsic duodenal obstruction: Clinical study and predictors of neonatal surgical mortality - Prmila Sharma; Naresh Pawar; Arun Kumar Gupta (EL-Med-Pub, 2022)
Background: This study was aimed to analyze the clinical profile and the predictors of neonatal surgical mortality of congenital intrinsic duodenal obstruction (CIDO). Methods: This is a case series of 67 patients with CIDO (duodenal atresia and stenosis) admitted at our teaching institute, from October 2018 to June 2020. The demographic data, clinical presentation, diagnostic methods, location & type of duodenal atresia, the operative procedure performed, and neonatal surgical mortality (NSM) predictors such as birth weight, age on presentation, associated anomalies, duration of surgery, extubation after surgery, sepsis, and vasopressors support were analyzed. Results: Of 67 patients, 40(60%) were premature; mean weight and age at presentation were 2.06±0.6 (1-8 kg) and 6.7(1-240days), respectively. The majority of patients (59, 88%) presented with vomiting, and the most common finding on the x-ray abdomen was a double bubble sign (54, 81%). Twenty-four (36%) were associated with congenital heart disease and 19(28%) had Down's syndrome. Type 3 duodenal atresia was the commonest finding in 43(64%) followed by type 1 in 22 (33%), and type 2 in 2(3%). In 49 (73%) Kimura's duodenoduodenostomy, excision of web & duodenoplasty in 13 (19%), and side to side duodenoduodenostomy in 4 (6%), were performed. The mean hospital stay of survivors was 9 days. Overall survival was 63%. Conclusion: Type 3 duodenal atresia is the commonest variety observed. The prematurity, low birth weight, associated major congenital anomalies, surgery >90 minutes, delayed extubation after surgery, sepsis, and need for vasopressors support are significant predictors of NSM.